The Distribution of Measles and Rubella in Health Office of East Java Province - Siti Rohmatul Laily; Santi Martini (Humanistic Network for Science and Technology (HNST), 2019)
Measles is a highly contagious disease caused by viruses that can be prevented by immunization and can be transmitted through coughing and sneezing. Measles is one of the five most common childhood diseases in the world. The purpose of this analysis is to describe the characteristics of measles cases in the East Java Provincial Health Office in 2018. This study was a descriptive study using a case report design, data obtained from measles case reports from 38 districts in East Java in January-December 2018. The sample in this study was all data on cases of measles suspicion reported in form C1. The data analysis test that will be used was using a descriptive test and chi-square test. Based on descriptive analysis test, it was found that measles cases were mostly in women (57.4%) and